The Macroeconomic Impact of Remittances: A Sending Country Perspective - Timo Baas; Silvia Melzer (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
Remittances are for a large number of developing countries the most important source of foreign funding. Destination countries of migration, however, fear a outflow of financial funds. Using data for Germany, we analyze the impact of remittances and migration on one of the major sending countries of remittances and the third biggest exporter in the world. For this purpose, we develop a dynamic open-economy general equilibrium model with altruistic households. By estimating the interrelation between household characteristics and remittances, we are able to derive altruism coefficients for different types of households. Households with a higher altruism coefficient derive higher utility from consumption by distant relatives and send more remittances. We endogenize remittances flows by applying these coefficients to our model. Remittance outflows have then a depreciating effect on the real exchange rate and provide incentives to reallocate resources from the non-tradable goods to the tradable goods sectors. In the case of Germany, this translates into a opposite Dutch disease phenomenon.
Keywords: F22; F24; D58; 330